Moderasi dalam Perspektif Feminis Dayak Ngaju dan Kitab Rut - Wirawan, Aprianto; Wainarisi, Yane Octavia Rismawati (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
Dayak Ngaju is one of the most prominent tribes in Central Borneo. From the beginning, the People of Dayak Ngaju lived with many different belief systems so even though they didn’t understand what moderation meant, they always live in that diversity all along their life. This research was to the women of Dayak Ngaju to observe their perspectives on religious moderation compared to the critical history of Ruth's author as a Bible text with women as a central figure. This research uses the qualitative method with an ethnography approach and a critical history of Biblica interpretation to express their paradigm about moderation itself. The result of this research points out how the women of Dayak Ngaju have a major tendency to be agents of moderation in Dayak Ngaju people because of the active connection of them in family and society like Ruth as center figure of the author of Ruth in the Old Testament.